Technology and Transition: 'Progressive Evolution of Regimes and the Consequences for Energy Regime Change. (June 2016) - Read, Stephen; Lindhult, Erik
Abstract: Transition of energy systems has been under-theorised. We have argued previously that energy efficiency as a strategy for fossil fuel replacement is inadequate as energy demand is not being reduced by efficiency alone. This paper is intended to elaborate further on the reasons. We require better answers to better questions about the nature of energy regimes and how they resist change. Our present-day socio-technical energy regime is a global integrated technical arrangement based on cheap high-yield energy sources (fossil fuels) with built-in 'progressive' social and economic directions. This 'progressive' change relies on cheap energy as a resource towards ever greater global integration and economic efficiency. Energy regime change will be not a tinkering at the edges but will require a dismantling of this 'progressive' tendency with radical retrogressive economic and social consequences. We conclude a change of our relationship with energy will require the reversal of a contingent 'progressive' tendency that is as old as mankind and the necessarily modest building of a new infrastructural apparatus designed to a new 'end', or the reversion to previous low or lower demand apparatus based on non-fossil energy sources. Both solutions would imply major social and economic changes which we will deal with in another paper.